Examining the Fintech Ecosystem of ASEAN-6 Countries - Zheng, Alice Huong Yong (Animo Repository, 2022)
Fintech is the driving force behind the digital economy, with the goal of improving cross-national interaction. However, the future development of Fintech in ASEAN-6 remains ambiguous, with little attention paid to an investigation. This study, therefore, aims to examine the Fintech ecosystem in ASEAN-6 countries by constructing a Fintech Index over the period of 2017 to 2019. This index consists of the readiness and capacity to participate in Fintech activity, the level of demand for Fintech services, and the possible future growth of Fintech. To achieve this objective, this study employs the averaging methods, that is, arithmetic mean, geometric mean, and entropy form. The results show that Singapore has the strongest Fintech ecosystem, followed by Thailand, Malaysia, Vietnam, Indonesia, and the Philippines. The findings imply that there is no single nation dominating the index by overlapping all aspects; ASEAN-6 countries are advised to resolve the major obstacles to enhance the Fintech development.